Body fluid derived exosomes as a novel template for clinical diagnostics - Keller, Sascha; Ridinger, Johannes; Rupp, Anne-Kathleen; Janssen, Johannes W. G.; Altevogt, Peter (Journal of translational medicine, 2011)
Exosomes are small membrane vesicles with a size of 40-100 nm that are released by different cell types from a late endosomal cellular compartment. They can be found in various body fluids including plasma, malignant ascites, urine, amniotic fluid and saliva. Exosomes contain proteins, miRNAs and mRNAs (exosome shuttle RNA, esRNA) that could serve as novel platform for diagnosis.